Determinants of treatment plan implementation in multidisciplinary team meetings for patients with chronic diseases: a mixed-methods study. Issue 10 (9th June 2014) - Raine, Rosalind; Xanthopoulou, Penny; Wallace, Isla; Nic a' Bháird, Caoimhe; Lanceley, Anne; Clarke, Alex; Livingston, Gill; Prentice, Archie; Ardron, Dave; Harris, Miriam; King, Michael; Michie, Susan; et al.
Abstract : Objective: Multidisciplinary team (MDT) meetings are assumed to produce better decisions and are extensively used to manage chronic disease in the National Health Service (NHS). However, evidence for their effectiveness is mixed. Our objective was to investigate determinants of MDT effectiveness by examining factors influencing the implementation of MDT treatment plans. This is a proxy measure of effectiveness, because it lies on the pathway to improvements in health, and reflects team decision making which has taken account of clinical and non-clinical information. Additionally, this measure can be compared across MDTs for different conditions. Methods: We undertook a prospective mixed-methods study of 12 MDTs in London and North Thames. Data were collected by observation of 370 MDT meetings, interviews with 53 MDT members, and from 2654 patient medical records. We examined the influence of patient-related factors (disease, age, sex, deprivation, whether their preferences and other clinical/health behaviours were mentioned) and MDT features (as measured using the 'Team Climate Inventory' and skill mix) on the implementation of MDT treatment plans. Results: The adjusted odds (or likelihood) of implementation was reduced by 25% for each additional professional group represented at the MDT meeting. Implementation was more likely in MDTs with clear goals and processes and a good 'Team Climate' (adjusted OR 1.96; 95% CI 1.15 to 3.31 for a unit increase in Team Climate Inventory (TCI) score). Implementation varied by disease category, with the lowest adjusted odds of implementation in mental health teams. Implementation was also lower for patients living in more deprived areas (adjusted odds of implementation for patients in the most compared with least deprived areas was 0.60, 95% CI 0.39 to 0.91). Conclusions: Greater multidisciplinarity is not necessarily associated with more effective decision making. Explicit goals and procedures are also crucial. Decision implementation should be routinely monitored to ensure the equitable provision of care.